THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE AND CEO GENDER ON TAX AVOIDANCE IN INDONESIA - Elfina Astrella Sambuaga (Sampoerna University, 2026)
This study examines the impact of Corporate Social Responsibility (CSR) disclosure and CEO gender on tax avoidance in non-financial sector companies listed on the Indonesia Stock Exchange from 2018 to 2021, also considering control variables such as leverage, company size, the COVID-19 pandemic, and profitability. Using a sample of 124 observations and multiple linear regression models, the findings indicate that CSR disclosure does not significantly affect tax avoidance due to the minimal implementation of CSR in Indonesian companies, where CSR activities are not mandated and are perceived to offer little benefit. Consequently, companies allocate low budgets for CSR activities, resulting in minimal disclosures. Additionally, the study finds that CEO gender does not significantly influence tax avoidance. The very low representation of female CEOs in Indonesian companies, with leadership predominantly held by males, contributes to this finding. As a result, CSR disclosures related to gender equality and equal employment opportunities are also low, leading to an insignificant impact on tax avoidance. Based on these results, the study suggests expanding the sample size by including more companies and extending the observation period in future research. Additionally, incorporating international companies could provide comparative insights into the influence of CSR and gender on tax avoidance. Researchers are advised to reduce subjectivity in dummy variable checklists for CSR and gender by conducting repeated and thorough checks. This study highlights the need for increased CSR implementation and greater gender diversity in leadership positions to potentially influence corporate tax practices positively.